Spin-coatable, photopatternable magnetic nanocomposite thin films for MEMS device applications. Issue 104 (11th November 2015) - Kandpal, M.; Sharan, C.; Palaparthy, V.; Tiwary, N.; Poddar, P.; Rao, V. Ramgopal
<x xml:space="preserve">Abstract</x> Magnetic nanomaterials' (especially metals) air stability and compatibility with standard micro-fabrication technologies are often a concern for development of MEMS-based magnetic devices.